The Importance of Whistleblowers in the Field of Environmental Crime Prevention - Kostic, Jelena Ž (NBP. Nauka, bezbednosti, policija, 2024)
Whistleblowing is an important activity not only for combating corruption, but also other irregularities and illegal actions. Protection of the enviornment is certainly a matter of public interest, and the prevention of crimes that violate its integrity is useful above all from the aspect of protecting peopleˋs lives and health. In a large number of cases, environmental crime is very difficult to detect and prove. The role of the whistleblower is of particular importance for the timely detection of environmental offenses and the reduction of occurence or mitigation of harmful consequences. In this paper, we start from the assumption that whistleblowers in the field of environmental protection are faced with a large number of challenges and arenˋt adequately protected. They are mostly either fired by their employer or forced due to various pressures to quit without the possibility of new employment. Considering the importance of their role in the field of environmental protection, the possibility of improving their postition should be reconsidered. In order to make recommendations for the improvement of both national regulations and practices related to the protection of whistleblowers, in this work we primarily use the method of content analysis, as well as the dogmatic-legal method.